2019
DOI: 10.1111/socf.12542
|View full text |Cite
|
Sign up to set email alerts
|

After the March: Using Instagram to Perform and Sustain the Women's March

Abstract: The January 2017 Women's March was an example of the paradigmatic March on Washington, part of the repertoire of collective action used by social movements in the United States for decades. Similar marches were held on its first and second anniversary, in January 2018 and January 2019, respectively. One did not need to travel to the nation's capital to participate in these marches, however; activists also organized hundreds of “sister marches” across the United States and internationally. Yet, a sole focus on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Where technology creates a channel of communication between social movement organizations and individual supporters, it may facilitate identification with the Resistance. Einwohner and Rochford (2019) analyze engagement with the Women's March Instagram account between the 2017 and 2018 marches. They find differences between the official account and Women's March hashtag users in the purpose of their posts and how they performed identity.…”
Section: #Resist: Communications Technology Distributed Organizing mentioning
confidence: 99%
“…Where technology creates a channel of communication between social movement organizations and individual supporters, it may facilitate identification with the Resistance. Einwohner and Rochford (2019) analyze engagement with the Women's March Instagram account between the 2017 and 2018 marches. They find differences between the official account and Women's March hashtag users in the purpose of their posts and how they performed identity.…”
Section: #Resist: Communications Technology Distributed Organizing mentioning
confidence: 99%
“…The citizen-consumer duality is arguably central to the study of social media platforms, which operate in a system where capitalism and democracy represent clashing sets of values (van Dijck et al, 2018). Despite the documented use of Instagram for political activism (among many others, see Einwohner & Rochford, 2019), the platform tends to promote so-called "commodity activism" (Mukherjee & Banet-Weiser, 2012) in the wider context of a life that must be "shoppable" (Hund & McGuigan, 2019). For example, while there is an active body positivity movement on Instagram (Cohen, Irwin, Newton-John, & Slater, 2019), brands and corporations exploit its visibility to engage in direct advertising, effectively silencing activists and reshaping the structure and goals of the movement itself (Cwynar-Horta, 2016).…”
Section: Investigating the Construction Of Values On Instagram: A Conceptual Roadmapmentioning
confidence: 99%
“…As technology has become more accessible, a growing area of research on collective identity and social movements has focused on collective meaning making and identity creation online. Numerous studies have found that collective identity forms in virtual spaces (Ackland & O’Neil, 2011; Ems, 2014; Einwohner & Rochford, 2019; Gal et al, 2016; Khazraee & Novak, 2018; Mundt et al, 2018; Ray et al, 2017; Rohlinger & Bunnage, 2018; see also Abul-Fottouh & Fetner, 2018; Castells, 2015). In their study of social media use within the Black Lives Matter movement, for example, Mundt, Ross and Burnett conclude that social media plays a significant role in “building connection, mobilizing participants and tangible sources, coalition building, and amplifying alternative narratives” (2018, p.1; see also Ems 2014).…”
Section: Introductionmentioning
confidence: 99%